Zebrafish Galectin 3 binding protein is the target antigen of the microglial 4C4 monoclonal antibody. Issue 3 (2nd November 2022) - Rovira, Mireia; Miserocchi, Magali; Montanari, Alice; Hammou, Latifa; Chomette, Laura; Pozo, Jennifer; Imbault, Virginie; Bisteau, Xavier; Wittamer, Valérie
Abstract: Background: Two decades ago, the fish‐specific monoclonal antibody 4C4 was found to be highly reactive to zebrafish microglia, the macrophages of the central nervous system. This has resulted in 4C4 being widely used, in combination with available fluorescent transgenic reporters to identify and isolate microglia. However, the target protein of 4C4 remains unidentified, which represents a major caveat. In addition, whether the 4C4 expression pattern is strictly restricted to microglial cells in zebrafish has never been investigated. Results: Having demonstrated that 4C4 is able to capture its native antigen from adult brain lysates, we used immunoprecipitation/mass‐spectrometry, coupled to recombinant expression analyses, to identify its target. The cognate antigen was found to be a paralog of Galectin 3 binding protein (Lgals3bpb), known as MAC2‐binding protein in mammals. Notably, 4C4 did not recognize other paralogs, demonstrating specificity. Moreover, our data show that Lgals3bpb expression, while ubiquitous in microglia, also identifies leukocytes in the periphery, including populations of gut and liver macrophages. Conclusions: The 4C4 monoclonal antibody recognizes Lgals3bpb, a predicted highly glycosylated protein whose function in the microglial lineage is currently unknown. Identification of Lgals3bpb as a new pan‐microglia marker will be fundamental in forthcoming studies using the zebrafish model. Key Findings: The 4C4 monoclonal antibody is highly specific for zebrafish Lgals3bpb, an ortholog of the MAC2–BP in mammals The 4C4 monoclonal antibody is suitable for western blotting and immunoprecipitation, in addition to immunofluorescence.